Gênese e desenvolvimento dos saberes pedagógico-tecnológicos na docência em Arquivologia (UFSM) frente à convergência digital - Barbiero, Danilo Ribas (2015)
This scientific research, conducted in the context of "Training, knowledge and professional development" Research Line, at the Doctorate Course on Education at the Graduate Program in Education at the Federal University of Santa Maria (UFSM), continues and extends the previous master research named "Between the Classroom and the Virtual: Movement Towards New Knowledge of higher education teaching" (BARBIERO, 2013). The study is the identification of two new knowledge of higher education: one is related to educational possibilities on the web, and the other is related to the use/integration of ICT on teaching-learning process; named as pedagogical-technological knowledge (PTK). We devise the thesis that the PTK, having its origin in the initial formation of the university professor and developed in classroom teaching, is improved on virtual teaching. The objective oj this research is to investigate the genesis and development of PTK of teachers in Archival Science (UFSM), with reference to digital culture and technological convergence. The specific objectives of the study are: mapping the configuration of PTK genisis in Archival Science (UFSM), bringing it close to ICT and the web; to characterize the configuration of PTK in Archival Science (UFSM) before virtual teaching, and to analyze the possible repercussion of virtual teaching in the [re] configuration of PTK in Archival Science (UFSM). On literature review we expanded the current knowledge of the subjec of that dissertation; deepening concepts as teacher training, teaching choreography, teaching in higher education, and studies related to contemporary sociodigital context. In this one, we approached digital culture and technological convergence, and studies on reflective collective intelligence. We have used a qualitative approach of a case study,in which, the starting point was the corpus consisting of oral interviews with teachers at the Documentation Department of UFSM, those who teach at Graduate Course in Archival Science (UFSM,) and at the Post-Graduate Course in Record Management (UAB/UFSM). The corpus received a new treatment of information, with the help of webQDA software and analytical improvement by discursive textual analysis. In the chapter of research findings, we have discussed the genesis and development of PTK in university education, in professional activities of classroom teaching, and virtual teaching. We also approached the development of Digital Technology Impermanence as characteristic of PTK in virtual teaching.